AML/CFT Regulation : Implications for Financial Service Providers that Serve Low-Income People - World Bank (Washington, DC, 2013)
This report on anti-money laundering (AML) and combating the financing of terrorism (CFT) regulation addresses the consequences of these regulations on low-income people. The introduction of new or tightened AML/CFT regulations may have the unintended and undesirable consequence of reducing the access of low-income individuals to formal financial services. As a means to avoid this outcome, this paper argues in favor of gradual implementation of new measures; the adoption of a risk-based approach to regulation; and the use of exemptions for low-risk categories of transactions.